1988
DOI: 10.1159/000263335
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fetal Blood Volume for Computer-Assisted Management of in utero Transfusion

Abstract: We performed 41 intravascular ultrasound-guided fetal transfusions in a total of 20 pregnancies with erythroblastosis fetalis or alloimmune thrombocytopenia. On the basis of this experience, we developed a computer-assisted procedure for determining the volume to be transfused, which provides an adequate final concentration. Fetal weight was estimated using ultrasound measurements. Fetoplacental blood volume was estimated from the regression line: fetoplacental volume (ml) = 1.046 + fetal weight (g) × 0.14. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 12 publications
5
36
0
1
Order By: Relevance
“…Previously, Mandelbrot et al 4 have observed similar differences in FPV values resulting from these two types of calculations. The calculation will over-estimate the FPV if the formula does not take into consideration the difference between donor and post-transfusion Ht (Equation 1) and it will under-estimate it if the end-transfusion FPV has increased with a volume less than the added donor blood volume (Equation 2) 4,5 .…”
Section: (Equation 1) Differ Significantly From Those Worked Out Withsupporting
confidence: 54%
“…Previously, Mandelbrot et al 4 have observed similar differences in FPV values resulting from these two types of calculations. The calculation will over-estimate the FPV if the formula does not take into consideration the difference between donor and post-transfusion Ht (Equation 1) and it will under-estimate it if the end-transfusion FPV has increased with a volume less than the added donor blood volume (Equation 2) 4,5 .…”
Section: (Equation 1) Differ Significantly From Those Worked Out Withsupporting
confidence: 54%
“…• 0.1 mL volume/g of estimated fetal weight [49], or • 0.15 mL volume/g of estimated fetal weight [50], or • 1.046 + (fetal weight in grams) x 0.14 [51].…”
Section: Intravascular Intrauterine Blood Transfusion (Iut)mentioning
confidence: 99%
“…In order to simplify these formulas, Giannina et al [49] introduced a simplified equation and compared this to previously described methods [51,52]:…”
Section: Intravascular Intrauterine Blood Transfusion (Iut)mentioning
confidence: 99%
“…There are equations available to help the clinician determine the appropriate intrauterine intravascular transfusion volume [7][8][9]. Although these equations are useful, they either require a readily available computer or an assistant to help perform the mathematics to rapidly and accurately ascertain the correct volume required during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Our first objective was to introduce a new method to estimate the appropriate volume of packed red blood cells to intravascularly transfuse an anemic fetus. Secondly, we compared the final fetal Hct values predicted from the transfusion volumes estimated using our new method with those obtained from two previously reported calculations [7,8].…”
Section: Introductionmentioning
confidence: 99%